Pore-forming peptide C14R exhibits potent antifungal activity against clinical isolates of Candida albicans and Candida auris - Vélez, Norida; Argel, Andreys; Kissmann, Ann-Kathrin; Alpízar-Pedraza, Daniel; Escandón, Patricia; Rosenau, Frank; Ständker, Ludger; Firacative, Carolina (Frontiers in Cellular and Infection Microbiology, 2024)
Invasive candidiasis is a global public health problem as it poses a significant threat in hospital-settings. The aim of this study was to evaluate C14R, an analog derived from peptide BP100, as a potential antimicrobial peptide against the prevalent opportunistic yeast Candida albicans and the emergent multidrug-resistant yeast Candida auris. Methods. Antifungal susceptibility testing of C14R against 99 C. albicans and 105 C. auris clinical isolates from Colombia, was determined by broth microdilution. Fluconazole was used as a control antifungal. The synergy between C14R and fluconazole was assessed in resistant isolates. Assays against fungal biofilm and growth curves were also carried out. Morphological alterations of yeast cell surface were evaluated by scanning electron microscopy. A permeability assay verified the pore-forming ability of C14R. Results. C. albicans and C. auris isolates had a geometric mean MIC against C14R of 4.42 µg/ml and 5.34 µg/ml, respectively. Notably, none of the isolates of any species exhibited growth at the highest evaluated peptide concentration (200 µg/ml). Synergistic effects were observed when combining the peptide and fluconazole. C14R affects biofilm and growth of C. albicans and C. auris. Cell membrane disruptions were observed in both species after treatment with the peptide. It was confirmed that C14R form pores in C. albicans' membrane. Discussion. C14R has a potent antifungal activity against a large set of clinical isolates of both C. albicans and C. auris, showing its capacity to disrupt Candida membranes. This antifungal activity remains consistent across isolates regardless of their clinical source. Furthermore, the absence of correlation between MICs to C14R and resistance to fluconazole indicates the peptide's potential effectiveness against fluconazoleresistant strains. Our results suggest the potential of C14R, a pore-forming peptide, as a treatment option for fungal infections, such as invasive candidiasis, including fluconazole and amphotericin Bresistant strains.